AMERICAN QUARTER HORSES’ BEHAVIORAL FORMS - USM ADMIN (Studia Universitatis Moldaviae: Stiinte reale si ale naturii, 2015)
The review of basic literary sources is made out of behavior of horse. On the basis of the field researches (visual supervisions) after three different aged groups of mares it is built ethograms. An ethogram of behavioral forms among mares was developed. They represent the different forms of mares’ behavior in a dynamics. The reaction of mares of the different age-related and physiology groups on appearance of extraneous objects on a pasture, their activity, hierarchy, socialization is analyzed in groups. Several main studies on equines were reviewed in ethogram. Four objects were placed into the pasture with the mares and foals including a mat, cone, halter, and mounting block. Initial interest of mares in objects was high. Herd mentality highly evident. When one horse spooked at object the whole herd followed. After 5 minutes, majority of mares and foals lose interest in objects. The major general behavior categories observed include: locomotion, comfort, and harem social. Dominance was demonstrated while looking at the objects. Dominance was also demonstrated when a mare wanted to be in a specific place or play with a specific toy, she would pin her ears back, bite, or kick at the other mare. Keywords: behavior categories, ethogram, open and pregnant mares, foal, American quarter horses, foals.